The Impact of a Transversus Abdominis Plane Block Including Clonidine Versus Intrathecal Morphine on Nausea and Vomiting After Caesarean Section: A Randomized Controlled Trial. Issue 2 (June 2020) - Dereu, D; Savoldelli, G.L.; Mercier, Y.; Combescure, C.; Mathivon, S.; Rehberg, B.
Abstract : ( Eur J Anaesthesiol . 2019;36:575–582) Pain management within the first 36 hours after cesarean section can have significant impact on postoperative maternal health and satisfaction. Inadequate pain relief may be associated with delayed breastfeeding and increased risk of postoperative complications. In addition, persistent pain at the 2-week postpartum mark is a risk factor for ongoing pain at 3 months postpartum as well as postpartum depression. Anesthesiologists often administer intrathecal morphine (ITM) during spinal anesthesia to manage postcesarean pain, but this approach often results in side effects such as postoperative nausea and vomiting (PONV) and pruritus; these adverse effects can considerably reduce maternal satisfaction. The current investigators conducted this study to determine if a transversus abdominis plane (TAP) block that included both local anesthetic and clonidine was a better pain management treatment compared with ITM in terms of PONV occurrence, other adverse effects, analgesic efficacy, and postoperative recovery quality.